"The Books of the Office of My Charge": A Case Study on the English Translation of a New Orleans Spanish Colonial Judicial Record. Issue 3 (June 2015) - Forsythe, Jenny Marie
Heloise Hulse Cruzat and Laura Louise Porteous spent decades of their lives feeding the quill and ink symbols scratched onto eighteenth century Spanish and French colonial judicial records to their typewriters. Cruzat worked for the Louisiana Historical Society (LHS) from 1917 to 1931 as a translator of French colonial records, and Porteous worked from 1920 to 1948 on the Spanish records. Translation was a central part of the process that transformed the colonial notarial and judicial records into historical documents. In this case study, one Spanish judicial record is compared to Porteous's corresponding English "Index" entry. Examining such work closely allows us to spotlight what Porteous chose to omit; moreover, her "Index" entry becomes a tool for reading between the lines of one Spanish colonial judicial record.